Water-Land-Food Nexus: Water Governance for Fish Production and Rice Farming - Sithirith, Mak; Sok, Sao; De Silva, Sanjiv; Kong, Heng; Kongkroy, Chay; Thavrin, Tim; Sarun, Hy (WorldFish, 2023)
Cambodia has abundant water resources in general, but it has a little water in the dry season. The increased dry season rice farming in many provinces, following the increased rice export policy in Cambodia and the spill-over effects of rice trade in Vietnam has led to high demands for water for dry season rice farming. These have led to water shortage and conflicts over water among farmers in the farming provinces, and between sectors, for instance, fishery and rice farming. Irrigation system development and improvement have improved water management and support to agricultural development. Rice farming areas have been expanded to around 2 million ha and rice farming has been increased from one rice crop to three rice crops a year. These have increased the high demand of waters for rice farming